Use of three-dimensional printing as a rehabilitation tool for individuals with deafblindness or vision impairment: a scoping review protocol. Issue 10 (16th October 2021) - Bleau, Maxime; Jaiswal, Atul; Holzhey, Peter; Aubin, Gabrielle; Do, Anna; Dumassais, Shirley; Mirmiran, Roxane; Tangkhpanya, Fatima; Wittich, Walter
ABSTRACT: Objective: This scoping review aims to synthesize evidence on the practices involving additive manufacturing, also known as three-dimensional printing, as a rehabilitation tool to assist individuals with deafblindness or vision impairment, and to identify which International Classification of Functioning, Disability and Health domains of functioning can be improved by its use. The goal is to inform health care professionals and family caregivers on how additive manufacturing may enhance the quality of life of people with deafblindness or vision impairment. Introduction: Deafblindness and vision impairment impact many life domains, such as access to information, communication, and mobility. The sense of touch is the main gateway for communication for individuals living with these impairments. Additive manufacturing is a promising technology for producing customized, tactile-based, low-cost tangible objects and devices that could improve the functioning of those with sensory impairment. Emerging studies explore the benefits of additive manufacturing in rehabilitation, education, and inclusion of people living with vision impairment, but very little is known about its use for the deafblind. Inclusion criteria: This review will consider studies that focus on the most widespread additive manufacturing technologies for the use of individuals living with deafblindness or vision impairment, their family caregivers, or professionals who provide their rehabilitation care. Methods: A comprehensive search of 10 databases (PsycINFO, MEDLINE, Global Health, PubMed, CINAHL, Embase, ERIC, Web of Science, Engineering Village, and Scopus) will be conducted. Screening of records will be done at the title/abstract level and at the full-text level by independent reviewers of the team.